PENGARUH IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS HALUOLEO - Riston G Ahmad (Journal Publicuho, 2019)
Due to the problem on how does organization climate influence employee performance faculty of social and politic Haluoleo University, this research aims to analyze whether organization climate influence employee performance or not by proof the hypotheses based  on empirical data from faculty of social and politic Haluoleo University, and to analyze significant level of organization climate to employee performance. This research tests several organization climate variable which includes individual autonomy dimension, sanction orientation, visibility of structure and motivation, and also employee performance variables that consist of productivity, served quality,  respond, responsibility, accountabilityIn this research, we use descriptive, verification, and correlation analysis to analyze causality of influences by using survey methods to measure and analyze how big the influences of organizational climate to employee performance in faculty of social and politic Haluoleo University. By quantitative approach and statistical test. Data had been collected by using a questionnaire as a primary instrument, interview, documentation, and literacy study as secondary data. Then, those data proceed by using determination and product correlation analysis. The result of this research showed that organizational climate has a strong, significant, a positive influence on employee performance in faculty of social and politic Haluoleo University. Organization climate becomes a dominant factor which influences the employee. This research also has proven that employee performance will raise when its organization climate getting better.